Arrow of God - Achebe, Chinua; Post, K.W.J. (Garden City, N.Y. Anchor Books, 1969)
Set in the Ibo heartland of eastern Nigeria, one of Africa's best-known writers describes the conflict between old and new in its most poignant aspect--the personal struggle between father and son.
It is a fiction.
Keywords: Fiction